Genome-Wide Identification of Seven Polyamine Oxidase Genes in Camellia sinensis (L.) and Their Expression Patterns Under Various Abiotic Stresses - Li, Mengshuang; Lu, Jing; Tao, Mingmin; Li, Mengru; Yang, Hua; Xia, En-hua; Chen, Qi; Wan, Xiaochun (Frontiers in Plant Science, 2020)
Polyamines (PAs) in plant play a critical role in growth and development and in response to environmental stress. Polyamine oxidase (PAO) is a flavin adenine dinucleotide dependent enzyme that plays a major role in PA catabolism. For the first time, PAO genes in tea plant were screened for the whole genome-wide and seven CsPAO genes were identified, which were named CsPAO1-7. Phylogenetic tree analysis revealed seven CsPAO protein sequences classed into three groups, including clade I, III, and IV. Compared with other plants, the tea plant lacked clade II members. Genetic structure and tissue specific expression analysis showed that there were significant differences among members of the CsPAO gene family. Among members of the CsPAOs family, CsPAO4 and CsPAO5 contain more introns and are highly expressed in various organizations. CsPAO1, CsPAO4, and CsPAO5 genes were cloned and expressed heterologously to verify theirs function. Heat map showed high response of CsPAO5 to drought stress, while CsPAO1 and CsPAO2 were sensitive to changes in nitrogen nutrition. Furthermore, exogenous abscisic acid (ABA) treatment indicated that the expression of most CsPAO genes in roots and leaves was significantly induced. In the root, Spm content increased significantly, while Put and Spd content decreased, suggesting that ABA has great influence on the biosynthesis of PAs. Anaerobic treatment of picked tea leaves showed that the decomposition of PAs was promoted to a certain extent. The above data help to clarify the role of CsPAO in response abiotic and nitrogen nutritional stresses in tea plants, and provide a reference perspective for the potential influence of PAs on the tea processing quality.